Peran Lingkungan Keluarga Dalam Membentuk Sikap Moderasi Beragama Pada Anak - Dian Rosela; Wahyu Mulyadi; Yayuk Kusumawati (Institut Agama Islam Daruttaqwa Gresik, 2025)
This study aims to examine the role of the family environment in shaping religious moderation attitudes in children in Nggeru Kopa Village, Palama, a multicultural area inhabited by communities of Islam, Catholicism, and Protestantism. In this context of diversity, the family plays a strategic role as the main agent in instilling values of tolerance, mutual respect, and peaceful coexistence. The study uses a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The subjects of the research include parents, community leaders, and elementary school children residing in the village. The findings show that families instill religious moderation through familial approaches, role modeling, and value education from an early age. This moderation practice is reflected in daily life, such as respecting differences in beliefs, engaging in interfaith communication, and participating in social activities together. Universal values such as empathy, honesty, and justice are also taught as part of character education. However, there are challenges faced, such as economic limitations and the influence of a closed social environment, which may hinder the internalization of moderation values. This study concludes that families play a crucial role in shaping moderate character in children within a pluralistic society. The implications of these findings suggest the need for strengthening family capacity through support programs and collaboration with educational institutions and local religious leaders to create an inclusive and harmonious social ecosystem.